Integration of naturalistic to optimize biology learning outcomes: A literature review - Limbong, Ulisa Ararolita; Ardiah, Ardiah; Muslimin, Ayu Isnaini Nor; Santika, Bobi Hanggoro Yogi; Dalambide, Muhammad Jolianda Saputra; Rizky, Muhammad (UNIVERSITAS LAMBUNG MANGKURAT, 2026)
Biology education emphasizes the importance of integrating multiple intelligences to optimize learning outcomes and foster meaningful learning experiences. Among these, naturalistic intelligence plays a key role in helping students connect biological concepts with real-world natural phenomena. This study aims to explore how naturalistic intelligence has been integrated into biology learning and its impact on students’ understanding, attitudes, and learning achievements. A literature review was conducted using 1.780 research articles published between 2019 and 2024 from databases such as Google Scholar. Based on inclusion exclusion criteria, 10 articles were selected for in-depth analysis. The results indicate that learning strategies integrating naturalistic intelligence such as outdoor learning, contextual field exploration, and environment-based project learning enhance students’ conceptual understanding, environmental awareness, and motivation. Most studies applied qualitative or mixed-method approaches, highlighting the importance of authentic experiences in strengthening biology learning outcomes. This study concludes that incorporating naturalistic intelligence supports holistic education by linking cognitive and affective domains, and recommends further research on technology-based and culturally contextualized applications of naturalistic intelligence in biology education.Abstrak. Pendidikan biologi abad ke-21 menekankan pentingnya integrasi berbagai kecerdasan untuk mengoptimalkan hasil belajar dan menciptakan pengalaman belajar yang bermakna. Di antara berbagai kecerdasan tersebut, kecerdasan naturalistik berperan penting dalam membantu peserta didik mengaitkan konsep biologi dengan fenomena alam di kehidupan nyata. Penelitian ini bertujuan untuk menelaah bagaimana kecerdasan naturalistik diintegrasikan dalam pembelajaran biologi serta dampaknya terhadap pemahaman, sikap, dan hasil belajar siswa. Kajian pustaka dilakukan terhadap 856 artikel penelitian yang terbit antara tahun 2019–2024 dari basis data Google Scholar. Berdasarkan kriteria inklusi eksklusi, diperoleh 10 artikel yang dianalisis secara mendalam. Hasil menunjukkan bahwa strategi pembelajaran yang mengintegrasikan kecerdasan naturalistik seperti pembelajaran luar ruangan, eksplorasi lapangan kontekstual, dan pembelajaran berbasis proyek lingkungan dapat meningkatkan pemahaman konsep, kepedulian lingkungan, dan motivasi belajar siswa. Sebagian besar penelitian menggunakan pendekatan kualitatif atau campuran, yang menegaskan pentingnya pengalaman otentik dalam memperkuat hasil belajar biologi. Kajian ini menyimpulkan bahwa integrasi kecerdasan naturalistik mendukung pendidikan holistik dengan menghubungkan ranah kognitif dan afektif, serta merekomendasikan penelitian lanjutan terkait penerapan berbasis teknologi dan konteks budaya dalam pembelajaran biologi.